2022
DOI: 10.1108/jgr-12-2021-0103
|View full text |Cite
|
Sign up to set email alerts
|

Linking corporate social irresponsibility with workplace deviant behaviour: mediated by moral outrage

Abstract: Purpose This study aims to examine the effects of external corporate social irresponsibility on organisational workplace deviant behaviours through the mediation of moral outrage (MO) among non-managerial employees. Design/methodology/approach The primary quantitative data was collected from a sample of 328 non-managerial employees working in banking, refinery, petroleum and power distribution companies in Pakistan. Partial least square-structural equation modelling was used to estimate the modelled relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Negative perceptions of CSR have proven to result in unfavorable organizational outcomes (Abbasi and Amran, 2023). Moreover, the prolonged effects of the pandemic have caused immense challenges to CSR practices and organizations' relationship with their employees (Cheng et al, 2022).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Negative perceptions of CSR have proven to result in unfavorable organizational outcomes (Abbasi and Amran, 2023). Moreover, the prolonged effects of the pandemic have caused immense challenges to CSR practices and organizations' relationship with their employees (Cheng et al, 2022).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…In respect to specific stakeholders, several scholars have stressed how narcissism in CEOs causes damage to employees and other organization members (Abbasi and Amran, 2023;Campbell and Siedor, 2016). In fact, Judge et al (2006) showed that narcissism is positively linked with intentional damage in workplaces.…”
Section: Ceo's Narcissism and Irresponsible Behaviormentioning
confidence: 99%
“…Antonetti, 2020;Valor et al, 2022), in firms' financial performance as well as in firms' reputation, trustworthiness and moral capital (e.g. Sun and Ding, 2021;Wang and Li, 2019), in firm's transaction costs (Feng et al, 2022) and in workplace deviant behaviors as a form of employee revenge (Abbasi and Amran, 2023). These important and far-reaching consequences may explain the increased interest of researchers and practitioners in understanding CSI antecedents [1].…”
Section: Introductionmentioning
confidence: 99%